PENGETAHUAN LOKAL PEMILIHAN JENIS POHON PADA SISTEM AGROFORESTRI ILENGI BERDASARKAN FAKTOR BIOFISIK, BENTANG ALAM DAN SOSIAL EKONOMI (Studi Kasus Pada Masyarakat Sekitar Kawasan Hutan Dengan Tujuan Khusus (KHDTK). Hutan Pendidikan di Desa Dulamayo Barat, Kecamatan Telaga, Kabupaten Gorontalo) - Hiola, Abdul Samad (MATOA : JURNAL ILMU KEHUTANAN, 2015)
Land use system which combining trees crop with food crop or livestock knowed as agroforesty system. Agroforestry system on landscape rainfeed at Village of Dulamayo Barat local community called "ilengi". Agroforestry ilengi over time formed like natural forest. Agroforestri ilengi as main sources livelihood local community. Therefore conducted researches about local knowledge of selection the tree species based on biophysical factors, landscape factors and social economic factors. The purpose of this study to know Agroforestri ilengi characteristics, farmers knowledge about the selection of tree species, The method used in this research by analyzing the the local user value index (LUVI). The result showed biophysical factors, socio-economic landscape and farmers as the main consideration in the selection of tree species in Agroforestri land ilengi.Key word : Ilengi sgroforestry system, selection of tree species